Insights into the diagenetic environment of fossil marine vertebrates of the Pisco Formation (late Miocene, Peru) from mineralogical and Sr-isotope data. (January 2018) - Gioncada, A.; Petrini, R.; Bosio, G.; Gariboldi, K.; Collareta, A.; Malinverno, E.; Bonaccorsi, E.; Di Celma, C.; Pasero, M.; Urbina, M.; Bianucci, G.
Abstract: The late Miocene Pisco Formation of Peru is an outstanding example of richness and high-quality preservation of fossil marine vertebrates. In order to reconstruct the fossilization path, we present new textural, mineralogical and Sr-isotope data of diagenetic minerals formed in correspondence of fossil specimens such as marine vertebrates and mollusks. These fossil specimens were found at Cerro los Quesos, in the Ica Desert, within the diatomaceous strata of the Pisco Formation. Dolomite, gypsum, anhydrite and Mn minerals are the main phases found, while the calcium carbonate originally forming the mollusk valves is replaced by gypsum. An early formation of dolomite and of Mn minerals, triggered by the modifications of the geochemical environment due to organic matter degradation, is suggested by the textural relationships and is confirmed by the Sr isotopic ratio of dolomite, which agrees with that of seawater at the time of sedimentation. Instead, gypsum Sr isotopic ratios indicate a pre-Miocene seawater-derived brine circulating within the sedimentary sequence as a source for Sr. Oxidation of diagenetic sulfide causing a lowering of the pH of porewater is proposed as an explanation for Ca-carbonate dissolution. The diagenetic chemical environment was, nevertheless, favorable to bone preservation. Highlights: We study the fossilization environment of the marine vertebrate Pisco Lagerstätte. We describe textural, mineralogical and Sr-isotope data of post-burial minerals. Dolomite Sr isotopic ratio agrees with seawater at the time of sedimentation. Gypsum Sr isotopic ratios suggest an older or modified seawater-derived brine. Preservation of bones was favored by a suitable diagenetic chemical environment.